Endovenous procedures in varicose veins - Kabnick, L. S.; Cayne, N.; Jacobowitz, G.; Lamparello, P.; Maldonado, T.; Rockman, C.; Adelman, M. (Phlebologie, 2008)
Over the past ten years endoveous treatment options for varicose veins have evovled considerably, offering clinicians a multitude of options to meet the needs of their patients. The endothermal ablation procedures have moved to the forefront as the choice modality for treating truncal reflux. Both radiofrequency ablation and endovenous laser ablation are widely accepted and interchangeable, showing comparable efficacy and safety. Although numerous endovenous laser wavelengths exist, the data indicates that the differences do not affect the efficacy or postoperative recovery of the procedure. The endovenous laser innovation that has shown early evidence of improved patient outcome is the jacket-tip fiber. The versatility of sclerotherapy makes it a critical component in the endovenous treatment of varicosities. Although not approved by the Food and Drug Administration (USA), the use of a foamed sclerosing agent is the fastest growing segment of sclerotherapy and an important treatment modality in the future of varicose vein treatment. Cutaneous lasers and intense pulse light devices contribute a crucial element, enabling clinicians to treat minute veins that may be impossible to treat with other therapies.
Keywords: Varicose veins; radiofrequency ablation; endovenous laser ablation; sclerotherapy